Finite element analysis in clinical patients with atherosclerosis. (January 2022) - Noble, Christopher; Carlson, Kent D.; Neumann, Erica; Lewis, Bradley; Dragomir-Daescu, Dan; Lerman, Amir; Erdemir, Ahmet; Young, Melissa D.
Abstract: Endovascular plaque composition is strongly related to stent strut stress and is responsible for strut fatigue, stent failure, and possible in-stent restenosis. To evaluate the effect of plaque on artery wall resistance to expansion we performed in silico analysis of atherosclerotic vessels. We generated finite element models from in vivo intravascular ultrasound virtual histology images to determine local artery surface stiffness and determined which plaque structures have the greatest influence. We validated the predictive capacity of our modeling approach by testing an atherosclerotic peripheral artery ex vivo with pressure-inflation testing at physiological pressures ranging from 10 to 200 mmHg. For this purpose, the in silico deformation of the arterial wall was compared to that observed ex vivo . We found that calcification had a positive effect on surface stiffness with fibrous plaque and necrotic core having negative effects. Additionally, larger plaque structures demonstrated significantly higher average surface stiffness and calcification located nearer the lumen was also shown to increase surface stiffness. Therefore, more developed plaques will have greater resistance to expansion and higher stent strut stress, with calcification located near the lumen further increasing stress in localized areas. Thus, it may be expected that such plaque structures may increase the likelihood of localized stent strut fracture.